The Effect of 1,3,4-Oxadiazol and 1,2,4-Triazole Compounds on Urease and Pepsin Enzymes - M. Abdnoor, Zahraa; R. Jber, Nasreen; Saadoon Abdul-Razaq, Aliaa (Al-Nahrain Journal of Science, 2024)
The helicobacter pylori affected urease and pepsin enzymes in the stomach, so the object of this study is to screen the effect of bis 1,3,4-oxadiazole and bis 1,2,4, triazole derivatives compounds on h-pylori urease enzyme in vitro. The results show that urease was inhibited by all produced compounds when the concentration increased. The most effective urease inhibitor is determined to be the compounds (A3e, A3c, A3d and B3c). The clinical study involved studying the pepsin enzyme activity level in H-pylori patients and control, the results found that the activity of pepsin elevated in h-pylori patients as compared with control.  The prepared compounds were screened on pepsin enzyme in vitro and showed that all the prepared compounds decreased the pepsin activity as the concentration increased. The nitrogen heterocyclic compounds. This study concludes that nitrogen-containing heterocyclic compounds have an important future in the treatment of Helicobacter pylori disease.